The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/hup.2490
|View full text |Cite
|
Sign up to set email alerts
|

Is there any difference in patterns of use and psychiatric symptom status between injectors and non‐injectors of mephedrone?

Abstract: Intravenous mephedrone use is associated with a higher risk of harmful drug use, elevated psychiatric symptom profile and increased possibility of mephedrone being considered as an addictive substance. These findings might be important in efficient treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
(100 reference statements)
1
9
0
Order By: Relevance
“…Nevertheless, NPS users showed higher scores on almost all subscales of the BSI. The overall elevated psychiatric symptom profile of NPS‐using patients confirms the assumption of our former study (Kapitány‐Fövény et al, ), namely, that the use of cathinone derivatives may be related to highly impaired mental states, and this psychiatric impairment cannot solely be explained by a history of opiate use. Furthermore, the fact that it is not distinct psychiatric disorders—such as anxiety, mood disorders, or OCD—that characterize these cases, but rather a general psychopathological severity, may underline the marked need for in‐patient psychiatric care even more.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, NPS users showed higher scores on almost all subscales of the BSI. The overall elevated psychiatric symptom profile of NPS‐using patients confirms the assumption of our former study (Kapitány‐Fövény et al, ), namely, that the use of cathinone derivatives may be related to highly impaired mental states, and this psychiatric impairment cannot solely be explained by a history of opiate use. Furthermore, the fact that it is not distinct psychiatric disorders—such as anxiety, mood disorders, or OCD—that characterize these cases, but rather a general psychopathological severity, may underline the marked need for in‐patient psychiatric care even more.…”
Section: Discussionsupporting
confidence: 86%
“…One study found that extracting codeine with the use of simple techniques and household appliances can yield different amounts of codeine and non-opioid analgesics in the extracted mixtures making it difficult to control the doses (Kimergård, Deluca, Hindersson, & Breindahl, 2016b). Understanding risk factors associated with medicine tampering may help implement harm reduction interventions and deliver treatment to specific populations of polysubstance users where the risk of harm is disproportionately great (Kapitány-Fövény et al, 2015;Kimergård et al, 2016a;Talu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Those include cardiovascular, gastrointestinal, and neurological side effects ( 233 , 246 ). Well-described effects are also jaw clenching, reduced appetite, increased body temperature, increased sweating, abnormal vision, dilated pupils, headaches, tachycardia, palpitations, hypertension, arrhythmias, chest pain, nausea, bruxism, teeth grinding (bruxism), rhabdomyolysis, and renal failure ( 247 ). An important dangerous side effect is the significant hyponatremia.…”
Section: Mephedrone and Methylonementioning
confidence: 99%
“…This is similar to that shown after acute MDMA consumption. It is supposed to be induced by a combination of sweating, electrolyte loss, and antidiuretic hormone secretion ( 247 ). The intranasal application of mephedrone is associated with a significant nasal irritation.…”
Section: Mephedrone and Methylonementioning
confidence: 99%